Assessment of effects of street connectivity on traffic performance and sustainability within communities and neighborhoods through traffic simulation. (April 2019) - Zlatkovic, Milan; Zlatkovic, Sarah; Sullivan, Tim; Bjornstad, Julie; Kiavash Fayyaz Shahandashti, Seyed
Highlights: Increasing street connectivity has different effects on meso and micro networks. Better distribution of traffic flows and better performance in meso networks. Reduced speeds in micro networks. Increased connectivity improves network sustainability. Abstract: Street connectivity measures the density of networks and directness of paths. Increasing street connectivity is one of the ways to increase network capacities, achieve a better distribution of traffic flows, improve accessibility and encourage the use of non-motorized traffic modes. This paper analyzes the effects of enhanced street connectivity on traffic performance and sustainability through transportation modeling of three community-scale (mesoscopic) and three neighborhood-scale (microscopic) networks in Utah. It discusses traffic performance and sustainability effects that increased street connectivity has on different types and sizes of networks simultaneously. The analysis was performed as a part of the Utah Street Connectivity Study. On the community-scale level, the results showed a significant reduction in network travel times and delays after the implementation of increased street connectivity alternatives. Increased street connectivity on the community-scale level was compared to street widening, and outperformed it in most cases. The distribution of traffic flows was more balanced in the networks with more connectivity, with a reduction in Vehicle Miles Traveled (VMT). This study relates street connectivity performance measures on different levels to the sustainability of transportation networks. It shows that increased connectivity, especially in neighborhoods, leads to more sustainable environments.